Desmoscolecids from sublittoral fine-sand of Pierre Noire (West Channel) (Nematoda, Desmoscolecida) - Decraemer, W. (Bull.Mus. natn. Hist. nat., Paris, 1979)
Locality: ; Cabinet:n1268
NeMys doc_id: 16989 NeMys doc_id: 6377